2004
DOI: 10.1111/j.1432-2277.2004.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of mycophenolate mofetil in liver transplant recipients with calcineurin inhibitor-induced renal dysfunction

Abstract: Long-term survival after orthotopic liver transplantation (OLT) is mainly influenced by adverse events caused by immunosuppression. Several studies have shown the efficacy of mycophenolate mofetil (MMF) in improving calcineurin inhibitor (C1)-induced nephrotoxicity with concomitant reduction or withdrawal of CI. In this prospective study we assessed the long-term effect and safety of MMF. Thirty-two OLT recipients with significant renal impairment due to either cyclosporine A (n = 25) or tacrolimus (n = 7) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Recently, the effectiveness and safety of a regimen with combination of minimal CsA and standard MMF doses in long-term liver transplant recipients was evaluated (Cantarovich et al, 2003;Koch et al, 2004;Pfitzmann et al, 2002b;Bunchman et al, 2001) and the results are encouraging (Pfitzmann et al, 2003;Hodge et al, 2002). Similar findings were noticed in heart transplant recipients (Baryalei et al, 2003).…”
Section: Mmf and Immunosuppressive Drug Combinations In Solid Transplsupporting
confidence: 68%
“…Recently, the effectiveness and safety of a regimen with combination of minimal CsA and standard MMF doses in long-term liver transplant recipients was evaluated (Cantarovich et al, 2003;Koch et al, 2004;Pfitzmann et al, 2002b;Bunchman et al, 2001) and the results are encouraging (Pfitzmann et al, 2003;Hodge et al, 2002). Similar findings were noticed in heart transplant recipients (Baryalei et al, 2003).…”
Section: Mmf and Immunosuppressive Drug Combinations In Solid Transplsupporting
confidence: 68%
“…The impact of MMF administration on patients presenting chronic CNI‐related toxicity has been discussed previously 3, 9, 13–19. However, the incidence of AR still represents a matter of concern.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the authors discouraged this approach 18. In the same issue of the Lancet and more recently, 4 studies in which MMF was administered as monotherapy14, 16, 17, 19 and 2 studies in which patients were still receiving small doses of prednisolone9, 13 showed more promising results (Table 4). However, in 2004 the group of Baltimore reported an incidence of irreversible AR of 23% in a group of 13 patients, leading to death (2×) and retransplantation (1×) 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations